Relationships between excessive gestational weight gain and energy and macronutrient intake in pregnant women. Issue 8 (August 2020) - Rugină, Cosmin; Mărginean, Cristina Oana; Meliţ, Lorena Elena; Giga, Dana Valentina; Modi, Viviana; Mărginean, Claudiu
Objective: This study aimed to compare energy and macronutrient intake, birth weight, and anthropometric parameters (mid-upper arm circumference or tricipital skin-fold thickness) between women who had adequate and excessive gestational weight gain (GWG) during pregnancy. Methods: We studied 115 pregnant women and divided them according to GWG into two groups: adequate GWG (n = 49) and excessive GWG (n = 66). We assessed the medical history, clinical examinations, and dietary habits through a detailed 7-day dietary recall using myfitnesspal software. Results: Weight, body mass index, mid-upper arm circumference, and tricipital skin-fold thickness were significantly higher at the time of delivery in women with excessive GWG compared with those with adequate GWG. A lipid-based diet was a risk factor for excessive GWG (relative risk: 1.488, 95% confidence interval: 1.112–1.991), whereas a protein-based diet was a protective factor (relative risk: 0.6723, 95% confidence interval: 0.4431–1.020). We found no significant relationship between a carbohydrate-based diet and GWG. The total energy intake was significantly higher in the excessive GWG group than in the adequate GWG group. Conclusions: Mainly a lipid-based diet in pregnant women might represent a risk factor for excessive GWG. However, a protein-based diet is a protective factor for excessive GWG.